Un nuevo hallazgo del nido del Burajara Común (Dysithamnus mentalis) (Passeriformes: Formicariidae) - Bosso, Andrés; Heinonen, Sofía; Chebez, Juan Carlos (El Hornero, 1988)
Este artículo no cuenta con un resumen.